Cultural heritage tourism at Saguaro National Park using the Community Capital Framework - Sautter, Jeremy (Kansas State University, 2011)
Community Capital Framework often provides a foundation for analyzing community development in cities and neighborhoods (Flora & Flora, 2008). However, the relationship between cultural heritage tourism and individual community capitals has been little studied in southern, Arizona. Therefore the primary objective of this study is to determine the most influential capitals at a renowned cultural heritage site in Arizona, Saguaro National Park. For this case study an assessment system will be established to assess the most influential capitals. Robert Stake’s The Art of Case Study Research was used as the research model to examine the relationships between cultural heritage tourism and the individual community capitals at Saguaro National Park. Results from this case study indicated that natural and cultural capitals appear to be the most influential because much of the monument’s development and community outreach revolve around the protection of the site’s Saguaros and their importance as a cultural heritage resource to the indigenous people of the Sonoran desert.
Keywords: Cultural heritage tourism; Community capital framework; Area Planning and Development (0341); Recreation and Tourism (0814)